The Current Formation Processes in Lithium Power Sources with SiO2 – C Composite Cathode - Myronyuk, I.F.; Sachko, V.M.; Mandzyuk, V.I. (Physics and Chemistry of Solid State, 2015)
The current formation process in lithium power source (LPS) with SiO2 –22% C composition cathode is explored in this work using galvanostatic cycling, cyclic voltammetry and impedance spectroscopy methods. It is set that specific capacity of LPS is 1757 mA∙h/g at its discharge in the mode C/20. Further cycling of LPS is accompanied by a sharp decline in specific capacity (irreversible capacity after the first cycle exceeds 95 %) due to formation of solid electrolyte interface of LiF composition and LiхSiO2 compound, in which lithium is not oxidized to the ion state during charging of source. It is found that the insertion of lithium ions into cathode material to the value x = 1,8 results in reduction of their diffusion coefficient on 4 orders (DLi = 2,2∙10 -14 ÷ 2,1∙10 -18 сm2/s).